Perancangan Sistem Penjualan Menggunakan Modul E-Commerce Pada Toko Tembakau Gentleman Paradise Berbasis Odoo - Maliki Naufal Rabbani; Mira Ziveria (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The Gentleman Paradise Tobacco Shop is a shop that has been engaged in sales since 1 year ago to be precise in June 2021, because of the high interest in purchasing tobacco cigarettes because the prices are cheap which has resulted in an increase in purchases at the Gentleman Paradise Tobacco Shop so that shop owners have difficulty in calculating stock of goods because they are still using the manual method. Therefore, the owner of the Gentleman Paradise Tobacco Shop asked for help in making a system that could make it easier in terms of calculating stock and sales, in solving these problems using ODOO in designing sales and stock counting systems and using the RAD Rapid Application Development method to simplify and speed up in the process of work and research